Go Forth and Tell : The Life of Augusta Baker, Librarian and Master Storyteller - McDaniel, Breanna J.; Harrison, April (New York : Dial Books for Young Readers, 2024)
A "picture book biography about librarian and storyteller Augusta Baker, the first Black coordinator of children's services at all branches of the New York Public library"--
Includes bibliographical references.
Keywords: Baker, Augusta, -- 1911-1998 -- Juvenile literature; Baker, Augusta, -- 1911-1998.; New York Public Library -- Biography; New York Public Library -- Biography; Children's librarians -- Biography -- United States; African American women librarians -- Biography -- United States; Storytellers -- Biography -- United States; Children's librarians; African American women librarians; Storytellers; Picture books; Biographies; Picture books